Interaksi Sosial Pedagang Kaki Lima dan Konsumen di JL. RE Martadinata: Social Interaction of Street Vendors and Consumers on JL. RE Martadinata - anidia, risma (Nirwasita: Jurnal Pendidikan Sejarah dan Ilmu Sosial, 2024)
This research aims to see how social interactions between street vendors and consumers at JL. RE Martadinata Banjarmasin. This research uses a qualitative method with observations as a data collection methods. This observation was carried out for 5 days in December 2023. This research observes 3 street vendors, pop ice sellers, pentol sellers and ice sellers. The research results show that social interaction between street vendors and consumers at JL. RE Martadinata or Pemerintah Kota (Pemko) Banjarmasin looks quite good. Pop Ice and pentol sellers look much more fulfilling for social interaction than ice sellers. Pop Ice sellers and Pentol sellers seemed to meet the social interaction indicators more in the early days of observation. Meanwhile, ice sellers seem to fulfill the social interaction indicators at the end of the day. Social interaction among street vendors not only plays a role in buying and selling transactions, but also plays an important role in the formation of broader social relationships.